Managerial Decision Making in Traffic - Perić, Teodor; Višnjić, Vinko; Perić, Dean (Promet - Traffic&Transportation, 2003)
Decision-making is defined as a selection of a certain actionamong several alternatives. It is the essence of planning, asin the managerial sense there is no plan until a decision of engagementof resources, reputation and direction of activities ismade. Decision-making is, in fact, only a step in planning, evenwhen it is performed quickly and without special consideration.It is what we all experience every day. It is one of the most fascinatingbiological activities and the subject of frightening implicationsfor the whole human race. Since various techniques improvethe system and the quality of managerial decision-making,they are classified into three assumptions: risk analysis, decision-making trees, and the theory of revealed preference. Allof these are based on the interaction of a certain number of importantvariables out of which many contain the elements ofuncertainty, but maybe also high level of probability.